Understanding Brick and Mortar Retailers’ Satisfaction and Continuous Intention of Mobile Payment Systems - Singh, Balgopal (Indian Journal of Marketing, 2024)
Purpose : This study aimed to understand the underlying dynamics of expectation-confirmation as an influencing factor of brick-and-mortar retailers’ satisfaction and continuous intention of the mobile payment system to enable the digital economy. Methodology : The research model and hypotheses in the context of mobile payment system continuous intention were developed associating the expectation-confirmation of technology usage, satisfaction, and continuance decision. Data were collected using a survey questionnaire from 452 brick-and-mortar retailers from different regions of India selected through multi-stage random sampling. Structural equation modeling (CB-SEM) was used to test the hypotheses. Findings : The study found strong evidence of positive disconfirmation on satisfaction and ex-post expectation from mobile payment usage influencing retailers’ continuous intention. Positive disconfirmation of ex-ante cognitive belief was found to positively affect satisfaction and lead to the development of more instrumental ex-post performance belief. Practical Implications : The findings of this study suggested that mobile payment service providers focus on delivering features that meet retailers’ expectations. The study also put forth the requisite of communicating credible claims through marketing promotions to shape genuine expectations from retailers’ mobile payment systems. Furthermore, the service provider must identify the retailers’ post-adoption expectation changes and focus on their continued satisfaction. Continued satisfaction ensures continuous acceptance of digital payments, enabling the digital economy. Originality : This study is the first to understand the underlying dynamics of retailers’ continuance intention of the mobile payment system. Also, it filled the gap in the extant literature, otherwise lacking an important participant of mobile payment network externalities.